Instructional Use of Virtual Reality in E-Learning Environments - Alfarsi G.; Bin Mohd. Yusof A.; Tawafak R.M.; Iqbal Malik S.; Mathew R.; Waseem Ashfaque M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Computer aided instruction; Education computing; Learning systems; Students; Virtual reality; E-learning environment; Education methods; Education sectors; Higher education; Professional development; Relevant documents; Students learning; Teaching methods; E-learning